(untitled) (Damascus University Journal for the basic sciences, 2025)
Administering medications through drinking water is a common and widely applied treatment method for both human and veterinary medications, and it may be the only treatment method for some medications, especially in intensive breeding conditions. Doxycycline is a tetracycline antibiotic that is commonly used for treatment in drinking water. Despite the positive aspects of this method of treatment, But it can carry many negatives, which are represented by the influence of many factors affecting the stability of doxycycline in treatment. This research aims to study the effect some factors have on the stability of doxycycline through 24 hours when used it as a water treatment. The effect of temperature, time, light, oxidants (H2O2-NaOCl), pH, and the effect of some cations dissolved in the water (Na+, Cu+2, Mn+2, Zn+2, Ca+2, Mg+2, Fe+3, Al+3) on the stability of doxycycline. The change on concentration of doxycycline was measured using ultraviolet (UV) spectroscopy. Results showed that the antibiotic was affected by the aforementioned factors to different degrees. The most severe were the effects of light, high temperatures, and the presence of cations, especially calcium and magnesium. As for oxidants, they didn’t have any significant effect when used in according to the internationally recommended proportions.